2018
DOI: 10.1097/mao.0000000000001626
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Related Resting State fMRI Functional Connectivity in Tinnitus Patients: Tinnitus Diagnosis Performance

Abstract: The associations between auditory-related networks are weakened in tinnitus patients, even if they have normal hearing. It is possible that rs-fMRI can be a tool for objective examination of tinnitus, by focusing the auditory-related areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…We have reported that the tinnitus patients showed less auditory‐related FC compared with the control group . When rs‐fMRI positive is defined as less than 9% of all possible connections between auditory‐related ROIs with a beta threshold of more than 0.7, the sensitivity of tinnitus diagnosis is 86%, the specificity is 74% . Because the older patients tend to decrease in the objective diagnostic yield for tinnitus, we examined the age‐related change of the auditory FC using the HCP database.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have reported that the tinnitus patients showed less auditory‐related FC compared with the control group . When rs‐fMRI positive is defined as less than 9% of all possible connections between auditory‐related ROIs with a beta threshold of more than 0.7, the sensitivity of tinnitus diagnosis is 86%, the specificity is 74% . Because the older patients tend to decrease in the objective diagnostic yield for tinnitus, we examined the age‐related change of the auditory FC using the HCP database.…”
Section: Discussionmentioning
confidence: 99%
“…The significance threshold was set at P < .05 (false discovery rate‐corrected). As auditory‐related regions, Heschl's gyrus, planum temporaleale, planum polare, operculum, insular cortex, and superior temporal gyrus were set as the ROI from our previous reports …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations